Panduan Pengukuran Perangkat Lunak Metode Function Point Serta Implementasinya pada Website Pemesanan Tiket Bus - Rizky Parlika; Ahmad Maghfur’ Ali; Ardiana Deka Maharani; Bregsi Atingsari Julastri; Syalum Marsya Pruista (Universitas Wahid Hasyim, 2023)
Measuring software quality is an important thing for software engineering. The purpose of applying measurements to software processes is to find out how complex and useful the software is. The measurement method used is Allan Albrecht's method, namely the Function Point Analysis method, which was developed by the International Function Point User Group (IFPUG). In this study, the authors measured the quality of a bus ticket booking website. Prior to the measurement stage, the authors compiled a module that contains the limitations of each point so that it can be used as a guide for scoring at each measurement stage, namely the stage of calculating the Crude Function Point (CFP) and Relative Complexity Adjustment Factor (RCAF). A calculator application is also made that can automatically calculate the total of function points so that it can make measurements easier. After the total Function Point value of the website is found, the total value can be used to predict the price or cost of making the software.